PENGENALAN EKONOMI DAN BISNIS ISLAM MELALUI PENCEGAHAN PENYEBARAN VIRUS COVID-19 DI DESA TAPOS II, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Purnama Putra Purnama Putra; Muhamad Ismail (SAHID EMPOWERMENT JOURNAL, 2023)
The Covid-19 pandemic, which has become a pandemic in Indonesia, still needs to be managed by looking for opportunities that continue to grow the economy, especially in rural areas. Tapos II Village, Tenjolaya District, Bogor Regency is one of the places where community service is carried out from August to September 2020. Counseling about the Covid-19 pandemic is also used to provide an introduction to Islamic Economics and Business. With this community service, benefits can be achieved regarding the prevention and treatment of Covid-19, and the introduction and understanding of Islamic Economics and Business